Insights into the efficient degradation mechanism of extracellular proteases mediated by Purpureocillium lilacinum - Xiujun Zhang; Yuhong Yang; Li Liu; Xin Sui; Ramon Santos Bermudez; Lushan Wang; Wenxing He; Huilian Xu (Frontiers in Microbiology, 2024)
Protease secretion is crucial for degrading nematode cuticles using nematophagous fungus Purpureocillium lilacinum, but the secretion pattern of protease remains poorly understood. This study aimed to explore the degradation mechanism of proteases by investigating the characteristics of protease secretion under various carbon and nitrogen sources, and different carbon to nitrogen (C:N) ratios in P. lilacinum. The results showed that corn flour as a carbon source and yeast extract as a nitrogen source specifically induced protease secretion in P. lilacinum. P. lilacinum produced significant amounts of gelatinase and casein enzyme at C:N ratios of 10:1, 20:1, and 40:1, indicating that higher C:N ratios were more beneficial for secreting extracellular proteases. Proteomic analysis revealed 14 proteases, including 4 S8 serine endopeptidases and one M28 aminopeptidase. Among four S8 serine peptidases, Alp1 exhibited a high secretion level at C:N ratio less than 5:1, whereas PR1C, PR1D, and P32 displayed higher secretion levels at higher C:N ratios. In addition, the transcription levels of GATA transcription factors were investigated, revealing that Asd-4, A0A179G170, and A0A179HGL4 were more prevalent at a C:N ratio of 40:1. In contrast, the transcription levels of SREP, AreA, and NsdD were higher at lower C:N ratios. The putative regulatory profile of extracellular protease production in P. lilacinum, induced by different C:N ratios, was analyzed. The findings offered insights into the complexity of protease production and aided in the hydrolytic degradation of nematode cuticles.